Rethinking rail track switches for fault tolerance and enhanced performance. (October 2017) - Bemment, Samuel D; Ebinger, Emma; Goodall, Roger M; Ward, Christopher P; Dixon, Roger
Railway track switches, commonly referred to as 'turnouts' or 'points, ' are a necessary element of any rail network. However, they often prove to be performance-limiting elements of networks. A novel concept for rail track switching has been developed as part of a UK research project with substantial industrial input. The concept is currently at the demonstrator phase, with a scale (384 mm) gauge unit operational in a laboratory. Details of the novel arrangement and concept are provided herein. This concept is considered as an advance on the state of the art. This paper also presents the work that took place to develop the concept. Novel contributions include the establishment of a formal set of functional requirements for railway track switching solutions, and a demonstration that the current solutions do not fully meet these requirements. The novel design meets the set of functional requirements for track switching solutions, in addition to offering several features that the current designs are unable to offer, in particular to enable multi-channel actuation and rail locking, and provide a degree of fault tolerance. This paper describes the design and operation of this switching concept, from requirements capture and solution generation through to the construction of the laboratory demonstrator. The novel concept is contrasted with the design and operation of the 'traditional' switch design. Conclusions to the work show that the novel concept meets all the functional requirements whilst exceeding the capabilities of the existing designs in most non-functional requirement areas.